Analisis Dampak Kehadiran Pasar Ritel Modern terhadap Pendapatan dan Keberlangsungan Usaha Pedagang di Pasar Tradisional Dompu - Nur Kamariah; Samsudin Samsudin; Sumarni Sumarni (ProBisnis : Jurnal Manajemen, 2026)
This study aims to analyze the impact of the presence of modern retail markets on the income and business sustainability of traders at the Dompu Traditional Market. The presence of modern retail such as minimarkets and supermarkets has changed the consumption patterns of the community, which has the potential to affect the economic conditions of traditional market traders. This study uses a quantitative approach with a survey method. The research population comprises all traders at the Dompu Traditional Market, totaling 673 people, with a sample of 88 respondents determined using the Slovin formula. Data were obtained through the distribution of questionnaires and analyzed using simple linear regression with the assistance of IBM SPSS Statistics 21. Before the analysis was conducted, the data were tested for validity, reliability, and classical assumption tests. The results of the study indicate that the presence of modern retail markets has a significant effect on the income of traders and the business sustainability of traders at the Dompu Traditional Market. The increasing competition causes changes in the number of customers, sales levels, as well as traders' ability to maintain their businesses. These findings indicate that the presence of modern retail becomes an important factor influencing the economic condition of traditional market traders. Therefore, policies and strategies are needed that can enhance the competitiveness of traditional market traders so they are able to survive amid the development of modern retail.